Manajemen Taman Kanak-Kanak Islam: Studi Teoritis Program Pembelajaran dan Hubungan Masyarakat - Nurhasan, Nurhasan (Didaktika Religia, 2015)
The great number of kindergartens in Indonesia shows great participation of public, foundations, and social charities. Such participation should always be enhanced by progressively increasing expectations. The essence of management is how to manage and take advantage of all available resources effectively and efficiently to achieve success as expected. Management of Islamic education meant here is an educational organization that is divided into different types of education with their own characteristics and purposes. All are trying to embody the values of Islam in the education system. In addition, Management of public relations is the management which governs the relationship between institutions and the public. Public relation has a considerable role for the development of an institution. That is to say, an institution may not develop properly without good relations with the surrounding community, especially educational institutions (pre-school or school). Educational institutions are an open system.